Investing in wet mills and washed coffee in Ethiopia: Benefits and constraints - Tamru, Seneshaw; Minten, Bart (International Food Policy Research Institute, 2018)
Local value-addition in developing countries is often aimed at the upgrading of agricultural value chains, since it is assumed that doing so will make farmers better off. However, transmission of the added value through the value chain and constraints to adoption of value-adding activities by farmers are not well understood. We look at this issue in the case of coffee in Ethiopia – the country’s most important export product – and value-addition in the coffee value-chain through ‘washing’ coffee, which is done in wet mills. Washed coffee is sold internationally with a significant premium compared to ‘natural’ coffee, and we find that this premium is largely transmitted to producers. However, while wet mills have become more widespread, the share of washed coffee in Ethiopia’s coffee exports is not increasing over time and, even if coffee farmers have access to a wet mill, they often do not sell all their coffee cherries to them. Relying on a unique primary large-scale dataset and a combination of qualitative and quantitative methods, we examine the reasons for this puzzle. The reasons seemingly are twofold. First, labor productivity in producing red cherries, which wet mills require, is lower than for natural coffee, reducing incentives for adoption, especially for those farmers with higher opportunity costs of labor. Second, only impatient, often smaller, farmers sell red cherries, as more patient farmers use the storable dried coffee cherries as a rewarding savings instrument, given the negative real deposit rates in formal savings institutions.